2019
DOI: 10.1021/acs.nanolett.9b04404
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Control over Terahertz Electromagnetic Interference Shielding with 2D Ti3C2Ty MXene by Ultrafast Optical Pulses

Abstract: High electrical conductivity and strong absorption of electromagnetic radiation in the terahertz (THz) frequency range by metallic 2D MXene Ti 3 C 2 T y make it a promising material for electromagnetic interference shielding, THz detectors, and transparent conducting electrodes. Here, we demonstrate that ultrafast optical pulses with wavelengths straddling the visible range (400 and 800 nm) induce transient broad-band THz transparency in the MXene that persists for nanoseconds. We demonstrate that optically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 77 publications
4
74
0
Order By: Relevance
“…Mochalin and Titova et al further demonstrated that 2D MXene Ti 3 C 2 T y holds promising potential for EMI shielding, THz detection, and transparent conducting electrodes. [ 116 ] Under ultrafast optical pulses of wavelengths straddling the visible range, MXene present transient broad‐band THz transparency for nanoseconds, with aspiration for designing new EM devices, such as sensitive optically gated detectors.…”
Section: Smart Electromagnetic Devicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Mochalin and Titova et al further demonstrated that 2D MXene Ti 3 C 2 T y holds promising potential for EMI shielding, THz detection, and transparent conducting electrodes. [ 116 ] Under ultrafast optical pulses of wavelengths straddling the visible range, MXene present transient broad‐band THz transparency for nanoseconds, with aspiration for designing new EM devices, such as sensitive optically gated detectors.…”
Section: Smart Electromagnetic Devicesmentioning
confidence: 99%
“…A variety of 3D architectures are emerging and making considerable development in EM functions, such as enhanced response, [ 37,47,77,79,101–107 ] multi‐function integration (hydrophobicity, flexibility, self‐cleaning, heat‐insulating, etc. ), [ 63,82,109,110,115,116 ] and flexible tunability (optical, electrical, and thermal regulation, genes sequencing, etc.). [ 60,96,111–115 ] Especially, some crucial physical models and formulas are proposed, such as EHP model, AICT model, and conductive‐network equation for charge transport, [ 48,49,58 ] equivalent‐circuit model for dipole polarization, [ 83 ] and capacitor‐like structure for interfacial polarization, [ 84 ] as well as competitive synergy of two factors (charge transport and dipole polarization) and four basics (interface scattering, microcurrent, micro‐antenna radiation, and dielectric relaxation) for EM energy conversion, [ 57,120,121 ] with in‐depth insight into function‐structure relationship.…”
Section: Overview and Outlookmentioning
confidence: 99%
See 3 more Smart Citations